Shopping Mall Culture in India: An Empirical Study on Consumer Preferences and Organized Retail Growth - G. Bhavanandan; S. Sudhagar (Journal of Applied Taxation and Policy, 2026)
This study examines the underlying dimensions of consumers’ shopping-mall evaluations in selected Indian urban markets. A quantitative, cross-sectional design was employed using a mall-intercept survey. Data were collected from 181 active mall shoppers through a structured questionnaire measured on a five-point Likert scale. Exploratory Factor Analysis was conducted to identify the latent dimensions represented by the observed mall-selection attributes. The Kaiser–Meyer–Olkin value of 0.782 and a significant Bartlett’s test of sphericity confirmed the suitability of the data for factor analysis. The analysis identified seven dimensions: Brand Assortment, Accessibility, Ambience, Service Quality, Entertainment Facilities, Pricing Perception, and Digital Integration. Together, these dimensions explained 68.24% of the total variance. Brand Assortment accounted for the largest proportion of variance at 21.85%, followed by Accessibility at 12.42% and Ambience at 9.43%. The remaining dimensions also formed distinct components of consumers’ evaluations, indicating that shopping malls are assessed through a combination of functional, experiential, economic, interpersonal, and technological attributes. The findings provide practical implications for tenant planning, accessibility improvement, facility management, customer service, entertainment provision, value creation, and digital-service development. However, because the study used convenience sampling and focused on selected urban malls, the findings should be interpreted as context-specific. Future studies should validate the factor structure using larger, more representative samples and confirmatory analytical methods.